Analysis of Health Service Program for Elderly Age in Payakumbuh City Padang Karambia Health Center - Mahaza; Erick Zicof; Tania Varera (Miracle Journal Get Press, 2024)
The elderly population is a group that is vulnerable to health problems, requires special attention, and appropriate service programs. Based on data from the Payakumbuh City Health Office, the coverage of elderly health services in 2019 was 94.1%, in 2020 there was a decrease to 63.2% and in 2022 it decreased again to 47.4%. This study aims to analyze the elderly health service program in an effort to improve elderly health services in the Padang Karambia Health Center working area. The research method involved qualitative and quantitative data collection through interviews with health workers, direct observation of the service process, and document analysis related to the elderly health program.The results showed variation in the availability and accessibility of elderly health services at Puskesmas Padang Karambia, with more attention focused on outpatient services than prevention and rehabilitation. Findings also revealed a need to improve coordination between health service units at the puskesmas to provide more integrated services for the elderly. In addition, the lack of specialized training for health workers in addressing the health needs of the elderly poses a challenge to optimal service delivery. The implications of this study emphasize the importance of improving human resources, coordination between service units, and specialized training for health workers in order to improve the quality of health services for the elderly  population  at Puskemas Padang Karambia in Payakumbuh City.